1988
DOI: 10.1111/j.1360-0443.1988.tb03025.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Prevalence of Psychiatric Disorders in Patients With Alcohol and Drug Problems ⋆

Abstract: A survey evaluated the lifetime and current prevalence of mental disorders in 260 male and 241 female patients seeking assistance with alcohol and drug problems at an addiction research facility. Information was gathered using the NIMH Diagnostic Interview Schedule (DIS) and computer diagnoses were generated according to DSM-III criteria. Women did not show higher rates of psychiatric disorders than men, contrary to widespread belief among professionals that female substance abusers manifest more psychopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(33 citation statements)
references
References 19 publications
1
30
0
2
Order By: Relevance
“…Also, there was an important lifetime comorbidity with depressive (over 70%), anxiety (40%), and personality disorders (about 50%), avoidant PD and borderline PD being the most frequent. These findings are largely supported by those reported elsewhere (Hesselbrock et al 1985;Ross et al 1988;Nace et al 1991;Kessler et al 1997;Hallman et al 2001). Some authors Cloninger et al 1981;Gilligan et al 1988) assumed that female alcoholism was a unitary disorder and that type II alcoholism was limited to men.…”
Section: Discussionsupporting
confidence: 81%
“…Also, there was an important lifetime comorbidity with depressive (over 70%), anxiety (40%), and personality disorders (about 50%), avoidant PD and borderline PD being the most frequent. These findings are largely supported by those reported elsewhere (Hesselbrock et al 1985;Ross et al 1988;Nace et al 1991;Kessler et al 1997;Hallman et al 2001). Some authors Cloninger et al 1981;Gilligan et al 1988) assumed that female alcoholism was a unitary disorder and that type II alcoholism was limited to men.…”
Section: Discussionsupporting
confidence: 81%
“…Differences between Poly-Substance Abusers and Pure Alcoholics When controlled for gender, poly-substance abusers had a higher frequency of anxiety disorders than pure alcoholics, in particular more frequent social phobia and PTSD. Ross et al [10] also found that poly-substance abusers had a higher frequency of all Axis I disorders, particularly anxiety disorders, compared with pure alcoholics. In a study from Iceland, poly-substance abusers had a higher frequency of anxiety disorders than pure alcoholics [3].…”
Section: Prevalence Of Axis I and Ii Disordersmentioning
confidence: 99%
“…As for gender differences in Axis I disorders among substance abusers, depression and anxiety disorders in particular are known to be higher among women than men [3,5,7,10,11]. The ECA study found that 65% of female and 44% of male alcoholics had psychiatric diagnoses [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…158 Similarly, in a Canadian general population survey, among women who were identified as problem drinkers (2.1% of all women), 42% and 15% had positive screening tests for anxiety and depression, respectively, in contrast to 11% and 5% of male problem drinkers (p Ͻ .001). 159 Studies of alcohol treatment populations have also demonstrated greater depression [160][161][162][163][164][165][166] and anxiety 161,163,164,[167][168][169] among women than men. However, depression and anxiety do not appear to be caused by problem drinking in women.…”
Section: Neurologic Effects Of Alcohol Women May Experiencementioning
confidence: 99%